(3HfGA GdebGeI GdaGWejI aj fbV GdQSGdI GdYKeGfjIs - (3CMeO Hf WGhSs; (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3GdfGRd Ydi GdNhGWa HGca GdThQGb hHYO aEf GHGYKeGf GdLGMX Ufa cJGHg GdeSei HGdQSGdI GdYKeGfjI s
(3BNQgG (B:s
(3hef SGe QhMfG Ve TGFeg GdRgQGA hGdMeO ddg hMOg gPG BNQ eG hLOJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI Mbhb (B(70 - (3O(B) s
Keywords: (3GdJGQjNs